Single beta-blocker or combined amiodarone therapy in implantable cardioverter-defibrillator and cardiac resynchronization therapy - defibrillator patients: insights from the German DEVICE registry - Wiedmann, Felix Tobias; Ince, Hüseyin; Stellbrink, Christoph; Kleemann, Thomas; Eckardt, Lars; Brachmann, Johannes; Gonska, Bernd-Dieter; Kääb, Stefan; Perings, Christian A.; Jung, Werner; Lugenbiel, Patrick; Hochadel, Matthias; et al. (Heart rhythm, 2023)
Background - Because of its antiarrhythmic potency and due to the lack of alternatives, amiodarone is often used for antiarrhythmic therapy in patients with implantable cardioverter-defibrillator (ICD) or cardiac resynchronization therapy-defibrillator systems. To date, robust data on the safety and clinical benefit of amiodarone therapy in these patients are missing. - Objective - The purpose of this study was to assess the periprocedural and postprocedural outcomes of combined therapy with beta-blockers plus amiodarone compared to treatment with single beta-blockers in the “real-life” cohort of ICD recipients of the German DEVICE registry. - Methods - A total of 4499 patients who underwent ICD implantation, revision, or upgrade in 49 centers participating in the German DEVICE registry were enrolled from March 2007 to February 2014. - Results - Amiodarone had no significant effect on the success of defibrillation testing. Early implantation-associated complications were similar between the groups. However, 1-year overall mortality was significantly higher in the beta-blocker plus amiodarone cohort (adjusted hazard ratio 2.09; P <.001). Interestingly, among the surviving patients, amiodarone was not associated with a significantly reduced risk of ICD discharges or syncopal events. Furthermore, the occurrence of ventricular tachycardia (VT) storm or incessant VTs and the number of patients scheduled for intracardiac ablation did not differ among both groups, whereas the rate of rehospitalization was lower in the cohort with only beta-blockers. - Conclusions - Although amiodarone has no adverse effect on the success of defibrillation testing, our data suggest an increased all-cause mortality under amiodarone therapy, especially in the subgroups of patients with sinus rhythm or severely reduced left ventricular function. In surviving patients, rates of arrhythmic events were comparable.
Online verfügbar 10. Dezember 2022, Artikelversion 28. März 2023
Gesehen am 15.06.2023